Assessment of Severity Scoring Indexes in mortality prediction of Severe Community Acquired Pneumonia - Spasovska, Katerina; Grozdanovski, Krsto; Rangelov Goran; Milenkovikj, Zvonko; Cvetanovska, Marija; Kapsarov, Kosta; Kuzmanovski, Nikola; Jakimovski, Dejan; Kasapinova, Katerina; Atanasovska, Emilija (My University, 2022)
Introduction: community acquired pneumonia (CAP) is a leading cause of morbidity and mortality worldwide. Approximately 8-36% require treatment in the intensive care unit (ICU) due to disease severity. Aim of the study: to asses the capacity of severity scoring indexes to predict the mortality of severe CAP. Methods: the study included 129 adult patients with CAP hospitalized at ICU of the University Clinic for Infectious Diseases in Skopje during a 3-year period. Primary outcome variable was 30-day in-hospital mortality. Demographic, clinical and biochemical parameters were recorded and seven severity scores were calculated: Charlson comorbidity Index, CURB 65, SCAP at admission, SAPS II and APACHE II after 24 hours, MPM and SOFA score during the first 48 hours. Receiver Operating Curve (ROC) analysis was performed and areas under the curve (AUC) were calculated for all analyzed severity indexes to evaluate their capacities to predict the mortality. Results: the mean age of studied patients was 61 year and 66,7% were males. An overall mortality was 43.4%. Charlson Comorbidity Index has higher value in non-survivors and it was associated with a poor outcome. All scores had significantly increased values among non-survivors, except CURB-65 that had similar results in both groups, with no statistical significance with the outcome. AUC for all scores had close values, ranging from 0.714 for APACHE II to 0.755 for SCAP. The highest AUC showed MPM and SOFA score when calculated at 48 hour after the admission, with values of 0.800 and 0.839 respectively. Conclusion: according to the results of our study, the most commonly used severity scoring indexes had strong ability to detect patients with pneumonia that had increased risk for poor outcome, but none of them showed to be superior over the others in pneumonia mortality prediction.
Keywords: community acquired pneumonia; severity scores; mortality